2015
DOI: 10.1016/j.rbmo.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone administration before IVF in poor responders: a prospective cohort study

Abstract: The use of dehydroepiandrosterone (DHEA) may improve ovarian stimulation outcomes in women of advanced reproductive age and could reduce embryo aneuploidy. In this prospective study, 48 women diagnosed with poor ovarian response received DHEA supplementation for at least 12 weeks. These women were compared with a group of poor responders (n = 113) who did not receive supplementation. During the study period, patients taking day 2 FSH and oestradiol were measured monthly before and after treatment. Stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 28 publications
0
31
0
4
Order By: Relevance
“…1) showed that a total of nine studies were eligible for the metaanalysis, included four RCTs [5][6][7][8], four retrospective studies [10,11,19,20] and one prospective studies [21]. Of the total of 1208 patients, 540 cases were in the DHEA group and 668 cases were in the control group.…”
Section: Retrieval Results and General Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…1) showed that a total of nine studies were eligible for the metaanalysis, included four RCTs [5][6][7][8], four retrospective studies [10,11,19,20] and one prospective studies [21]. Of the total of 1208 patients, 540 cases were in the DHEA group and 668 cases were in the control group.…”
Section: Retrieval Results and General Characteristicsmentioning
confidence: 99%
“…With respect to the cancellation rate of IVF cycles, five retrospective studies [10,11,21] and one RCT [8] were eligible. No differences in the cancelled cycles were demonstrated between the DHEA and control groups [OR = 0.74, 95% CI: 0.51-1.08].…”
Section: Cancellation Rate Of Ivf Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…Для синхронизации роста фолликулов в программах ВРТ в течение пяти дней до начала стимуляции овуляции назна-чались антагонисты ГнРГ [26]. Также с целью улучшения ответной реакции яичников на сти-муляцию вводимыми извне гонадотропинами в течение двух менструальных циклов на этапе, предшествующем лечению, и во время проведе-ния протокола ЭКО назначался дегидроэпиан-дростерон (ДГЭА) [27][28][29]. В качестве подготов-ки к лечению в программах ВРТ на протяжении различных по продолжительности периодов и в вариабельных дозировках применялся те-стостерон, соматолиберин и соматотропный гормон (СТГ), эстрогены, L-аргинин, силдена-фил и миоинозитол [29][30][31][32][33][34][35][36][37][38].…”
unclassified